Experimental Design in Quantitative Research: Concepts, Types, Comparisons, and Applications - Amilia Fitri; Fauzah Nurul Hasilah; Salwa Salsabila Maaris; M. Faiz Azmi Ibnu Mansur; Ilham Hidayatul Ramadhani; Bayu Bambang Nur Fauzi (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
This study aims to describe the concept, types, comparisons, and applications of experimental design in quantitative research. The study employed a qualitative approach using the library research method. Data were collected through documentation techniques from books, scientific journals, and other relevant references related to experimental design. The data were analyzed using content analysis to identify, classify, and interpret the characteristics of various experimental designs. The findings indicate that experimental design is an essential research framework for examining causal relationships between variables. Experimental design consists of three main forms, namely pre-experimental design, quasi-experimental design, and true experimental design, each having different levels of control, validity, and applicability. Among these, true experimental design has the highest internal validity, while quasi-experimental design is the most frequently applied in educational research due to its practicality in real settings. Therefore, selecting an appropriate experimental design is crucial for producing valid and reliable research findings.